The social practices of hosting P2P social dining events: Insights for sustainable tourism, - Davies, Anna; Cretella, Agnese (My University, 2020)
In many ways, the expansion of commercial for-profit, P2P social dining platforms has mirrored those within mobility and accommodation sectors. However its dynamics and impacts have received less consideration to date, with a notable paucity of attention to the hosts of social dining events. The aim of this paper is to address this research lacuna. Through its exploration of the social dining platforms VizEat in Athens and Eatwith in Barcelona, this paper identifies, analyses and compares the social practices of hosts around their social dining events in two key tourist destinations in Europe. Data is gathered through multiple methods from participating in and observing social dining events in each city to interviews with key stakeholders in the P2P social dining process (such as hosts, platform employees and ambassadors). The research reveals how dynamic rules, tools, skills and understandings shape and reshape the performance of hosting social dining events. It exposes tensions and ongoing negotiations between hosts and guests regarding matters of authenticity and privacy, an uneven risk burden between hosts and platforms with regards liability and scant regard for matters of sustainability. As a result there is little alignment between P2P social dining and the goals of sustainable tourism.
PUBLISHED
Keywords: Social dining; tourism; social practice; sustainability; P2P platforms; Smart & Sustainable Planet; sustainable food